Points of Coincidence and Common Fixed Points for II-Expansive Mappings on Complex Valued Metric Spaces (Analysis in Theory and Applications, 2017)
We use the two mappings satisfying II-expansive conditions on complexvalued metric spaces to construct the convergent sequences and prove that the uniquelimit of the sequences is the point of coincidence or common fixed point of the twomappings. Also, we discuss the uniqueness of points of coincidence or common fixedpoints and give the existence theorems of unique fixed points. The obtained resultsgeneralize and improve the corresponding conclusions in references.
Keywords: Complex valued metric space; II-expansive mapping; Cauchy sequence; point of coincidence; common fixed point.